2019
DOI: 10.14814/phy2.14255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term exercise training for different durations on pancreatic amylase activity and intestinal glucose transporter content in rats

Abstract: Long‐term endurance training for a relatively short duration (~1 h) is reported to increase pancreatic amylase activity in rats, suggesting that chronic exercise training enhances carbohydrate digestive capacity. However, it remains unknown whether longer exercise training duration results in greater adaptation in the pancreas and small intestine. Thus, this study aimed to examine the effects of long‐term endurance training for a longer duration on pancreatic amylase activity and intestinal glucose transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Therefore, we assumed that the exercise-induced trend toward increased GLUT2 and SGLT1 in this study was induced via GLP-2 signaling. It has been reported that 6 wk of swimming training increased the expression of SGLT1, which was explained as an adaptation of the intestine to long-term exercise [15]. As the exercise style of this study was treadmill running, whereas that of the previous study was swimming, it was not possible to make a general comparison; however, GLP-2 might be a key factor in the adaptation of the intestine to exercise.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Therefore, we assumed that the exercise-induced trend toward increased GLUT2 and SGLT1 in this study was induced via GLP-2 signaling. It has been reported that 6 wk of swimming training increased the expression of SGLT1, which was explained as an adaptation of the intestine to long-term exercise [15]. As the exercise style of this study was treadmill running, whereas that of the previous study was swimming, it was not possible to make a general comparison; however, GLP-2 might be a key factor in the adaptation of the intestine to exercise.…”
Section: Discussionmentioning
confidence: 66%
“…Motiani et al reported that 2 wk of moderate intensity training increased the expression level of glucose transporter 2 (GLUT2) in the intestine of mice [14]. In addition, Kondo et al reported that 6 wk of swimming exercise induced substantial adaptations in the digestive capability of the pancreas and absorptive capability in the small intestine in rats [15]. Therefore, exercise might be effective in improving the digestive and absorptive molecules of carbohydrates in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we assumed that the exercise-induced increase of GLUT2 and SGLT1 in this study might be mediated via GLP-2 signaling. Six weeks of swimming training were reported to upregulate SGLT1, deemed as an adaptative response of the intestine to long-term exercise [15]. The present study explored the effects of a 1 h treadmill run as a form of acute exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Motiani et al reported that two weeks of moderate-intensity training upregulated the expression of glucose transporter 2 (GLUT2) in the intestines of mice [14]. Kondo et al reported that six weeks of swimming exercise induced substantial alterations in pancreatic digestive capability as well as in the absorptive capability of the small intestine in rats [15]. Therefore, exercise might be effective in improving the digestion and absorption of carbohydrates within the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Among the known symptoms of digestive enzymes deficiency are food intolerances, poor nutrient absorption, a weaker immune system, weight gain and obesity, skin and digestive problems, etc. Moreover, long-term endurance training for a long duration causes changes in the activity of digestive enzymes (e.g., pancreatic amylase) [ 184 ]. The supplementation of digestive enzymes by athletes is, apart from a method to alleviate unpleasant symptoms, one of the methods of improving sports performance.…”
Section: The Inhibition Of Digestive Enzymes By Polyphenolic Compoundsmentioning
confidence: 99%